Analisis Kecamatan Prioritas untuk Pembangunan Sarana dan Prasarana di Kawasan Pasca Tambang Timah Kabupaten Bangka Selatan (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2018)
Tin-mining has raised the local economy and income of South Bangka Selatan Regency, thus should have contributed to the development of infrastructure around tin-mine areas in the province. Positive impacts of tin-mining to infrastructure have not always been received by area around the tin-mine. The aim of this research is to determine priority districts for infrastructure development at post tin-mine areas in South Bangka Regency. The methods of the research were on-screen digitation, Scalogram and TOPSIS. The results of research shows that the land area of post tin-mine in South Bangka Regency covers 11,224.8 hectares, with Toboali District as the widest (5,053.3 hectares). Districts with the the most number of villages in hierarchy 1 was Toboali District (4 villages), while in hierarchy 3 was Air Gegas District (6 villages). Tin-mining has not always given positive effects to the development of regional infrastructure around tin-mine areas. Villages at Air Gegas Village and Toboali District are the priorities of infrastructure development, thus infrastructure development around tin-mining areas will be done equitable and gradually to resolve limited fund for future.